8.2k views
3 votes
If f(x) = 2x3 - 4x2 + 2, and g(x) = x3 - 2x2 - 2x + 4, then f(x) - g(x) =

User EMC
by
6.4k points

2 Answers

6 votes
2x^3-4x^2+2-x^3+2x^2+2x-4

x^3-2x^2+2x-2


User Paolo Constantin
by
6.8k points
1 vote

Answer:

f(x) - g(x) = x³ - 2x² + 2x -2.

Explanation:

Given : f(x) = 2x³ - 4x² + 2 and g(x) = x³ - 2x² - 2x + 4.

To find : f(x) - g(x) .

Solution : We have f(x) = 2x³ - 4x² + 2 and g(x) = x³ - 2x² - 2x + 4.

f(x) - g(x) = 2x³ - 4x² + 2 - ( x³ - 2x² - 2x + 4).

f(x) - g(x) = 2x³ - 4x² + 2 - x³ + 2x² + 2x -4.

Combine like terms

f(x) - g(x) = 2x³ - x³ - 4x² + 2x² +2x + 2 -4.

f(x) - g(x) = x³ - 2x² + 2x -2.

Therefore, f(x) - g(x) = x³ - 2x² + 2x -2.

User Oria Gruber
by
5.7k points